KEADILAN DALAM POLIGAMI MENURUT HUKUM ISLAM DAN PERSPEKTIF MASYARAKAT KOTA SABANG - Fera Marisa; Imran Imran; Hendra Surya (AL-ILMU, 2022)
As with the marriage system in Indonesia, which adheres to a monogamous system, there is also another system, namely the polygamous system where a husband may have more than one, two, three or more wives. The scholars differ on the provisions and laws of polygamy. Among them there are those who approve of polygamy and there are also those who prohibit polygamy, except out of necessity (as rukhshah) under certain conditions. What is certain is that Islamic law does not prohibit polygamy absolutely (haram) and also does not recommend absolutely (mandatory). Some opinions state that the principle of justice in polygamy is not just quantitative justice, such as giving material or rotating time between wives, but includes qualitative justice, namely love which is the foundation of domestic life. The purpose of this research is to find out the meaning of the fair concept of polygamy according to Islamic law and also to find out how to apply polygamy correctly according to Islamic law today. Based on the data from the analysis, it can be concluded that in principle Islamic law allows polygamy in a marriage with various fairly strict requirements, polygamy is prescribed as other provisions of Islamic law are for the benefit of mankind. From this it must be realized that a man may practice polygamy as long as he can realize the benefit. However, if he cannot realize the benefit of doing polygamy, then he is prohibited from polygamous. The concept of fairness in polygamy is not only difficult to live by, but contains more harm than good. The difficulty of creating a harmonious life, because humans will in essence always feel lacking. And Fair in polygamy is very difficult to live in today's life.Keywords: Justice, Polygamy, Law, Islam, and Society.